Microstructure-driven annihilation effects and dispersive excited state dynamics in solid-state films of a model sensitizer for photon energy up-conversion applications - Goudarzi, Hossein; Koutsokeras, Loukas E.; Balawi, Ahmed H.; Sun, Cheng; Manolis, Giorgos K.; Gasparini, Nicola; Yuan, Peisen; Antoniou, Giannis N.; Athanasopoulos, Stavros; Tselios, Charalampos C.; Falaras, Polycarpos; Varotsis, Constantinos; et al. (My University, 2023)
Bimolecular processes involving exciton spin-state interactions gain attention for their deployment as wavelength-shifting tools. Particularly triplet–triplet annihilation induced photon energy up-conversion (TTA-UC) holds promise to enhance the performance of solar cell and photodetection technologies. Despite the progress noted, a correlation between the solid-state microstructure of photoactuating TTA-UC organic composites and their photophysical properties is missing. This lack of knowledge impedes the effective integration of functional TTA-UC interlayers as ancillary components in operating devices. We here investigate a solution-processed model green-to-blue TTA-UC binary composite. Solid-state films of a 9,10 diphenyl anthracene (DPA) blue-emitting activator blended with a (2,3,7,8,12,13,17,18-octaethyl-porphyrinato) PtII (PtOEP) green-absorbing sensitizer are prepared with a range of compositions and examined by a set of complementary characterization techniques. Grazing incidence X-ray diffractometry (GIXRD) measurements identify three PtOEP composition regions wherein the DPA:PtOEP composite microstructure varies due to changes in the packing motifs of the DPA and PtOEP phases. In Region 1 (≤2 wt%) DPA is semicrystalline and PtOEP is amorphous, in Region 2 (between 2 and 10 wt%) both DPA and PtOEP phases are amorphous, and in Region 3 (≥10 wt%) DPA remains amorphous and PtOEP is semicrystalline. GIXRD further reveals the metastable DPA-β polymorph species as the dominant DPA phase in Region 1. Composition dependent UV-vis and FT-IR measurements identify physical PtOEP dimers, irrespective of the structural order in the PtOEP phase. Time-gated photoluminescence (PL) spectroscopy and scanning electron microscopy imaging confirm the presence of PtOEP aggregates, even after dispersing DPA:PtOEP in amorphous poly(styrene). When arrested in Regions 1 and 2, DPA:PtOEP exhibits delayed PtOEP fluorescence at 580 nm that follows a power-law decay on the ns time scale. The origin of PtOEP delayed fluorescence is unraveled by temperature- and fluence-dependent PL experiments. Triplet PtOEP excitations undergo dispersive diffusion and enable TTA reactions that activate the first singlet-excited (S1) PtOEP state. The effect is reproduced when PtOEP is mixed with a poly(fluorene-2-octyl) (PFO) derivative. Transient absorption measurements on PFO:PtOEP films find that selective PtOEP photoexcitation activates the S1 of PFO within ∼100 fs through an up-converted 3(d, d*) PtII-centered state.
Keywords: As-spun state; Composite DPA:PtOEP flms; Films